Adaptability, forage yield and nutritional quality of alfalfa (Medicago sativa) genotypes. Issue 1 (1st January 2021) - Atumo, Tessema Tesfaye; Kauffman, Richard; Gemiyo Talore, Deribe; Abera, Mergia; Tesfaye, Temesgen; Tunkala, Bereket Zeleke; Zeleke, Muluken; Kebede Kalsa, Getinet
ABSTRACT: Livestocks fed with high-quality forage deliver better milk and meat, which could benefit the nutritional health of their keepers and consumers. Six alfalfa genotypes were assessed across four locations, Arba Minch, Areka Mante Dubo, Bonga and Hawassa Dilla, for adaptability, forage dry matter (DM) yield, crude protein (CP) concentration, nutrient composition and digestibility characteristics from August 2016 to January 2019. The genotypes were evaluated in a randomized complete block design with four replications. Plant height at forage harvest was significantly (P < 0.001) varied across the environment among genotypes. Nutrient components, such as neutral detergent fiber, acid detergent fiber and lignin, hemicelluloses, in vitro DM digestibility and relative feed value, were significantly (P < 0.01) different for genotype variations. The highest mean DM yield was recorded for FGI-9001 followed by FGI-3054. The highest plant height was recorded for FGI-8091 (60.13 cm), while the shortest genotype was FGI-1011. CP yield was recorded above the threshold level for all genotypes in the test. Highest in vitro DM digestibility and relative feed value with the lowest neutral detergent fiber, acid detergent fiber, and lignin and cellulose contents were recorded for FGI-9001. Tested alfalfa genotypes varied in terms of forage yield and nutritional quality at different locations. Thus, the result indicates the potential of genotypes, indicating the promotion to advanced varietal evaluation stages including animal test and release as better alternatives for use in the farming system in rain fed condition and irrigation.